ANALYSIS OF LEADERSHIP STYLES IN THE ANTASARI KOREM 101 ENVIRONMENT - Ari Aryanto; Ahmad Ahmad; M. Riza Firdaus (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Leadership is the process of influencing organized group activities to achieve goals. The success and failure of a leader is determined by the nature and style of leadership in directing the dynamics. Group. Through the leadership style of a leader, he will transfer several values such as group emphasis, support from people/employees, tolerance to risk, wage criteria and etc. This article aims to analyze the leadership style in Korem 101 Antasari. The method used in this study is a qualitative descriptive method. Participants in this study are 5 Kodim Commanders in Korem 101 Antasari Banjarmasin who are determined using purposive sampling with the consideration that they have served as Kodim Commanders in Korem 101/Antasari with a term of office of more than2 years.Data were collected through telephone interviews and analyzed using qualitative descriptive methods.Based on the research results, it can be concluded that theleadership style applied at Korem 101 Antasari Banjarmasin is a combination of Transformational, Strategic, Humanistic, humble, and Banjar culture-based leadership.